Development of Multimedia-Assisted E-LKPD Based on Problem-Based Learning to Improve Mathematical Problem-Solving Abilities and Independent Learning of Junior High School Students - Khairunnisa’ Nabilah; Kms.Muhammad Amin Fauzi; E. Elvis Napitupulu (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to develop a valid, practical, and effective multimedia-assisted problem-based E-LKPD (Electronic Student Worksheet) to improve mathematical problem-solving abilities and learning independence among junior high school students. In addition, this study analyzes improvements in students' mathematical problem-solving abilities through the use of the E-LKPD. The method used is development research with the ADDIE model, which was implemented at SMP Negeri 11 Medan. The research instruments include expert validation sheets, teacher and student response questionnaires, mathematical problem-solving ability tests, and learning independence questionnaires. The results of the study indicate that the developed E-LKPD meets the criteria of